UPAYA MENINGKATKAN KETERAMPILAN KOLABORASI SISWA KELAS V SEKOLAH DASAR DALAM PEMBELAJARAN MATEMATIKA MELALUI MODEL COOPERATIVE LEARNING TIPE QUICK ON THE DRAW - Rahmadina, Siti; Iva Sarifah; Linda Zakiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This class action research was conducted to improve students' collaboration skills in learning Mathematics through the application of the Cooperative Learning Type Quick On The Draw model for grade V students. This class action research was conducted at SDN Kramat Pela 07 Kebayoran Baru. The subjects of this study were class V-A students totaling 23 students. The classroom action research model used in this study is the Kemmis and Mc. Taggart model. Data on students' collaboration skills in learning Mathematics in cycle I reached 65.2%, then in cycle II it increased to 82.6%. The conclusion of this study is that the application of the Cooperative Learning Type Quick On The Draw model can improve collaboration skills in learning Mathematics in class V-A students of SDN Kramat Pela 07 Kebayoran Baru, so that teachers can use the Cooperative Learning Type Quick On The Draw model as an alternative to improve student collaboration skills in learning Mathematics.